PENGARUH UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI PREDIKSI VARIABEL PEMEDIASI ( Studi Empiris perusahaan yang terdaftar di BEI) - Toto Sudibyo; Nurkhayati Nurkhayati (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
The aim of this research is to understand the direct or indirect impact of corporate size on firm value, with corporate social responsibility (CSR) disclosure serving as an intervening variable. The research employs a purposive sampling method with specific criteria, selecting 50 companies as samples to represent all those listed on the Indonesia Stock Exchange. The analysis method utilized in this research is SPSS. The findings indicate that the size of the industry does not significantly influence CSR disclosure positively. However, the effect of CSR on firm value is significantly positive, while the impact of size on firm value is significantly negative. Additionally, CSR disclosure, as an intervening variable, is substantiated in this research.